Mel Frequency Cepstral Coefficient (MFCC) extraction for speaker identification on FPGA - Phak Len, Eh Kan; Rafikha Aliana, Raof; Ahmad Nasir, Che Rosli; Razaidi, Hussin (Universiti Malaysia Perlis, 2009)
Organized by School of Mechatronic Engineering (UniMAP) & co-organized by The Institution of Engineering Malaysia (IEM), 11th - 13th October 2009 at Batu Feringhi, Penang, Malaysia.